Effect of a Fast Potential Change on the Early Stage of Zinc Passivation in a Saturated Calcium Hydroxide Solution - Garnica-Rodríguez, Armando; Montoya, R.; Rodríguez-Gomez, Francisco Javier; Pérez-López, Tezozomoc; Genesca, Juan (Frontiers in Materials, 2022)
The fast and sharp corrosion potential change from the active state to the passive state, that pure zinc plates immersed in calcium hydroxide saturated solutions with and without chlorides spontaneously exhibit at the early stage of passivation, was studied. The corrosion behavior was investigated by corrosion potential monitoring, anodic polarization curves and electrochemical impedance spectroscopy. The zinc surface was characterized by scanning electron microscopy and X-ray energy dispersive spectroscopy. Experimental results show that the presence of chlorides increases the rate of change of potential by 10-fold in the early stage of passivation, producing a porous passivating film of corrosion products mainly made of calcium hydroxy-zincate Ca(Zn(OH)3)2· 2 H2O, with a less protective barrier effect than the non-porous film formed without chlorides. On the other hand, a modeling approach was achieved by solving the transient 2D Nernst–Planck equations and considering 12 chemical species. Numerical results confirm that the composition of the chemical products generated on the Zn surface certainly depends on the concentration of Cl¯ ions: Simonkolleite and hidroxides become unstable in the presence of high Cl¯ concentrations, whereas calcium hydroxyl-zincate is the main chemical compound generated on the Zn surface. However, the presence of the latter compound is much more important in electrolytes with very low concentration of Cl¯ ions.